The Paradox of Family Structure and Plans after Work: Why Single Childless Employees May Be the Least Absorbed at Work - Dumas, Tracy L.; Perry-Smith, Jill E. (Academy of Management Journal, 2018)
Existing research has shown that positive family experiences can affect work positively. In this article, however, we consider how family may enhance work even when family experiences are not explicitly positive. We draw on boundary theory and cognitive psychology’s current concerns theory to evaluate how employees’ family structures and associated after-work activities affect their work absorption. A survey of business school alumni (Study 1) revealed that single, childless workers reported lower absorption than workers with other family structures. Further, a daily diary study of university employees (Study 2) showed that employees’ planned after-work activities explained the relationship between family structure and work absorption. Specifically, single, childless workers anticipated fewer domestic after-work activities, resulting in lower work absorption. Due to similarities between domestic responsibilities and work tasks—for example, their obligatory and goal-directed nature—anticipating domestic responsibilities after work reinforces, rather than distracts from, the work mindset, thus keeping employees more immersed psychologically in their work. This finding suggests that having a spouse and/or children can affect employees’ work absorption positively through the anticipation of domestic duties after work. Thus, our study contributes to a more comprehensive view of how employees’ work and nonwork lives are connected.